1999
DOI: 10.1029/1998gl900166
|View full text |Cite
|
Sign up to set email alerts
|

Unusual composition of the solar wind in the 2–3 May 1998 CME observed with SWICS on ACE

Abstract: Abstract. Elemental, isotopic and charge state abundances provide valuable information about the source and acceleration mechanism of Coronal Mass Ejections (CMEs). Even though the kinetic properties of the plasma might be subject to changes because of dynamic effects occurring during the expansion of the CME, the composition of the solar wind remains unchanged after it leaves the low corona. Data from the Solar Wind Ion Composition Spectrometer (SWICS) on ACE are used to study the elemental and charge state c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 9 publications
4
56
0
Order By: Relevance
“…[Schwenn et al, 1980;Rakowski et al, 2007], being present. For these candidate ions, Gloeckler et al [1999] compared the charge state distribution in a CME event with that in slow solar wind as measured by ACE. The results indicated that in the CME the density of He + obviously increased.…”
Section: Observational Resultsmentioning
confidence: 99%
“…[Schwenn et al, 1980;Rakowski et al, 2007], being present. For these candidate ions, Gloeckler et al [1999] compared the charge state distribution in a CME event with that in slow solar wind as measured by ACE. The results indicated that in the CME the density of He + obviously increased.…”
Section: Observational Resultsmentioning
confidence: 99%
“…IMPACT field and electron measurements, coupled with PLASTIC measurements of the plasma ion composition, can be used to distinguish the magnetic fields in the filamentary material from those of other parts of the ICME structure, and examine their relationship, an important step toward resolving the source region question (e.g. Gloeckler et al 1999).…”
Section: The Solar Magnetic Cyclementioning
confidence: 99%
“…Observations of soft X-ray loops as well as of chromospheric flare ribbons indicate that reconnection occurs initially along highly sheared loops and only later do the magnetic field lines make a transition to more potential arcade loops (Canfield et al 2000;Martin & McAllister 1995;Su et al 2006) in a manner explained by models where reconnections take place initially in a sheared magnetic core (e.g., Moore et al 1997). A further analysis of flare ribbons implies that the bulk of magnetic cloud poloidal flux originates in reconnecting field lines (Qiu et al 2007), and studies of magnetic cloud charge states indicate possibly flare-associated heating along prominence-mass-carrying field lines (Skoug et al 1999;Gloeckler et al 1999;Reinard 2005). These observations indicate that the flux rope that escapes in the CME is made up of field lines that have undergone significant reconnection, as would be the case if the flux ropes were formed in situ during eruption, but which would not be the case for a pre-existing rope expanding in its entirety upwards without significant change of topology/connectivity.…”
Section: Introductionmentioning
confidence: 99%